Maine’s High- Risk Infants and Maternal Health and Wellbeing: The Maine Infant Follow-Up Project - Logan, Beth; Hayes, Marie; Brown, Mark; Tisher, Paul; Paul, Jonathan; Krishnan, Ramesh (Maine Policy Review, 2009)
The Maine Infant Follow-Up Project is a research-based effort to accelerate early identification of developmental risk for infants whose mothers use drugs or alcohol. These infants are at high risk for neurodevelopmental disorders, and early identification will enable early-early intervention. Targeted interventions will increase the chance for children to catch up developmentally during the period of most rapid brain growth in the first three years of life.
Keywords: Maine; high-risk infants; opiate addiction